Torrefaction of Empty Fruit Bunches: Evaluation of Fuel Characteristics Using Response Surface Methodology. Issue 1 (May 2020) - Helwani, Z; Zulfansyah; Fatra, W; Fernando, A Q; Idroes, G M; Muslem; Idroes, R
Abstract: Empty Fruit Bunches (EFB) can be used as an alternative energy source by torrefaction process. Torrefaction is a treatment process of biomass into solid fuel within temperature range of 200-300 °C in an inert condition. This research aims to study the effect of process variable interaction process and to study the characteristic of solid fuel resulted. Torrefaction of EFB was performed by using horizontal fixed bed reactor at three different temperatures, times and particle sizes, that are 225, 250 and 275 °C, for 15, 30 and 45 minutes, and particle size 2, 4 and 6 cm, respectively. Response surface methodology (RSM) was used for to optimization optimize of torrefaction conditions so that biofuel of with high energy density, maximum energy properties, and minimum weight loss could be manufactured. The analysis showed that increase in heating values was affected by treatment severity (cumulated effect of temperature, time and particle size). Our results clearly demonstrated an increased degradation of the material due to the combined effects of temperature and treatment time. While the reaction time had less impact on the energy density of torrefied biomass, the effect of reaction temperature was considerably stronger under the torrefaction conditions used in this study. The most significant factor affecting all responses was temperature of torrefaction, then followed by time and particle size. The optimized torrefaction conditions were verified empirically and the applicability of the model was confirmed. The torrefied biomass occurred more suitable than raw biomass in terms of calorific value, physical and chemical properties.